A new training package (3Cs: Connect, Communicate and Collaborate) for improving family responsive service delivery in early intervention for children with hearing loss: A proof of concept study. (January 2021) - Alduhaim, Alyaa; Purcell, Alison; Cumming, Steven; Doble, Maree
Abstract: Background: An objective of early intervention for children with hearing loss is to enhance family engagement in therapy to maximise a child's speech and language potential. However, requiring a service provider to work collaboratively with a child's family can create problems in developing and underdeveloped countries, where skilled service providers and services for children with hearing loss are lacking and where an expert model of intervention prevails. Objectives: To determine the preliminary effectiveness of a new training package Connect, Communicate and Collaborate (3Cs), in improving the knowledge and confidence of service providers in the delivery of family responsive services in an early intervention program for children with hearing loss. Methods: Five learning modules were developed based on service provider experience working with children with hearing loss, and parents of children with hearing loss. Six participants completed the training package comprising five training modules and an introductory session over a 6-week period. Participants' confidence and knowledge in providing family responsive practice was measured pre and post training using visual analogue scales, and participants were also invited to provide their reflections on the program. Results: Pre- and post-training confidence ratings revealed significant improvements in the perceptions of participants in the implementation of responsive family practice across four of five of programme learning modules (p < 0.002). Participant reflection statements indicate they became more considerated in their family responsive practice. Despite positive experiences working with parents, participants stated they had ongoing difficulties guiding families through the decision-making processes of habilitation. The reflection process assisted learning and improved practice by supporting participants to build on their strengths. Conclusion: The 3Cs package improved the confidence in and knowledge of delivery of responsive family services for six participants in Kuwait. It also improved the participant's self-evaluation skills. The 3Cs provides professional development that meets the needs of service providers working with children with hearing loss to improve inclusion of families in the therapy process.